Species diversity of Ganoderma (Ganodermataceae, Polyporales) with three new species and a key to Ganoderma in Yunnan Province, China - He, Jun; Han, Xiao; Luo, Zong-Long; Li, E-Xian; Tang, Song-Ming; Luo, Hong-Mei; Niu, Kai-Yang; Su, Xi-jun; Li, Shu-Hong (Frontiers in Microbiology, 2022)
Ganoderma is a globally distributed genus that encompasses species with forestry ecological, medicinal, economic, and cultural importance. Despite the importance of this fungus, the studies on the species diversity of Ganoderma in Yunnan Province, China (YPC) have poorly been carried out. During this study, opportunistic sampling was used to collect 21 specimens of Ganoderma from YPC. Morphology and multigene phylogeny of the internal transcribed spacer (ITS) regions, the large subunit of nuclear ribosomal RNA gene (nrLSU), the translation elongation factor 1-α gene (TEF1-α), and the second largest subunit of RNA polymerase II (RPB2) were used to identify them. Morphological and molecular characterization of the 21 specimens showed that they belong to 18 species of Ganoderma, of which three are novel viz. G. artocarpicola, G. obscuratum and G. yunnanense. Ganoderma artocarpicola is characterized by the sessile and concrescent basidiomata, reddish brown to yellowish brown pileus surface, heterogeneous context, wavy margin, and ovoid basidiospores. Ganoderma obscuratum is distinguished by small pores (6–9 per mm), dorsolaterally sub-stipitate basidiomata which become greyish-brown when dry, and narrow ellipsoid basidiospores. Ganoderma yunnanense is characterized by cream color pore surface and context, centrally to laterally stipitate basidiomata with reddish-brown to violet-brown strongly laccate pileus surface, and broadly ellipsoid basidiospores. With the help of an extensive literature survey and the results of this study, a checklist of 32 Ganoderma species from YPC was established, which accounts for 71.11% of the known species in China. In addition, a key to the Ganoderma in YPC is also provided.